Students’ understanding in making decision on a socioscientific issue within a co-curricular context / Mastura Halim - Mastura , Halim (2018)
The issue of the gap in research on the socioscientific issues and co-curricular context exists internationally. In global and Malaysian perspectives, socioscientific issues are difficult to solve; thus, it is important that students are exposed to informal learning circumstances through the co-curricular context. The co-curricular context as a learning environment is identified as a less explored area. Consequently, it possesses inadequate structure and guidelines that hinder its proper implementation, development, and significance. Therefore, this study aimed to explore the students’ understanding in making a decision on global warming issue within co-curricular context using a generic research paradigm. The participants were chosen based on the purposive sampling technique. This study involved 30 students (7th – 9th grades) of the Science and Mathematics Society from a Fully Residential School located in Selangor. It was conducted for six months. The related documents, interviews and observations were utilised as data collection techniques. The primary document used in this study is the Persuasive Graphic Organiser (PGO). It was developed by the researcher to explore students’ understanding in making decisions on the global warming issue. The PGO provides an appropriate visualised method for students in the aspects of understanding and performing decision-making skills on the socioscientific issues. The PGO evaluation process involved professional reviews from socioscientific and qualitative experts and orderly administered to students aged 13-15. The data were analysed using the constant comparative method. Four categories emerged when exploring the students’ understanding of global warming issue. The findings describe the students’ ability in 1) defining the global warming phenomena in terms of temperature and Green House Gasses (GHG) emissions, 2) identifying anthropogenic and natural factors affecting global warming, 3) clarifying the global warming effects in the aspects of health, ecological system and climate change, and 4) providing alternative solutions for the global warming phenomena in the aspect of sustainable development. This goes beyond formal curricular specification where students were traced as having sophisticated understanding in the global warming issue. The understanding is important for the students to draw conclusions using scientific and social considerations. The considerations of the students’ decision-making were grounded from the dimensions of environment, technological advancements, medical, economy, politics and religion. The study also reveals four factors which explain the influences of the co-curricular context towards promoting the students’ understanding in making decisions related to global warming issue. They are learning flexibility, socioscientific instructional materials, integrative activities and student readiness. Three conclusions can be drawn from the study. First, socioscientific understanding can be identified through the students’ ability in recognising relevant science knowledge. Second, socioscientific decisions can be drawn upon multi-dimensional considerations according to the specificity of context. Finally, the co-curricular setting can be used to complement socioscientific learning. Practical and methodological implications regarding the integration of socioscientific issues in the co-curricular context are also discussed.